Modeling Buffer Stock Money : An Appraisal. (IMF Working Papers; Working Paper ;, 1988)
The buffer stock role of absorbing temporary discrepancies between purchases and sales is assigned to money because money, being the most liquid of all assets, performs the buffer function best. However, as this paper shows, the attempts to model the buffer stock role have led to certain incoherencies. Specifically, this paper shows that the econometric models of buffer stock money published in the literature are incompatible with the theory of buffer stock money and imply two different probability distributions for the same variable, thus resulting in an incoherency.